Open defecation practice among households with latrines in rural communities of Ararso District, Somali Region, Eastern Ethiopia - Ismail, Abdifatah Mohamud; Ibrahim, Musse Ahmed; Abdi, Mahammoud Mohammed; Geremew, Abraham; Mulugeta, Yohannes; Ayele, Dinku Mekbib; Cheru, Abera (Frontiers in Public Health, 2024)
Background: Open defecation contributes to the spread of different feco-oral diseases. Therefore, access to a latrine is strongly recommended as it considerably reduces the risks. Even though, provision of latrine facilities alone does not guarantee the desired health benefits and should be integrated with behavior change. In Ethiopia, efforts have been made to increase the coverage of latrine facilities. However, evidence on how consistently the households use is limited. Most prior studies focused on latrine utilization among households, and limited evidence is available about open defecation practices among households with latrines and associated factors. Thus, this study is critical for developing effective intervention approaches to prevent open defecation among households with latrines.To assess the open defecation practice and associated factors among households with latrines in rural communities of Ararso district,